Teknologi Pengolahan Kandungan Kromium dalam Limbah Penyamakan Kulit Menggunakan Proses Adsorpsi: Review - Maryudi; Aster Rahayu; Refah Syauqi; Muhammad Kresna Islami (Jurnal Teknik Kimia dan Lingkungan, 2021)
The waste management issue is one of the biggest problems in the industries recently. Every industry has a high probability of releasing toxic by-product to the environment in the form of waste. One example is in the leather tanning industry. Leather tanning waste still removes harmful metals in its waste, such as heavy metal chromium (Cr). Chromium is used to produce finer skin products. About 30-40% chromium will be carried in the tanning liquid waste. The high chromium levels remaining and carried away in the waste can cause acute and chronic toxicity to the environment and even very harmful to living things. Adsorption is one of the highly recommended methods available to overcome this problem. Relatively low handling costs, simple processes, and the possibility of being recycled are some of the adsorption process's advantages. In addition, the adsorption process can be maximized by using adsorbents that have specific potential specifications for chromium absorption. This article reviews batch and continuous adsorption methods in the processing of chromium content in tannery waste.